Identification and measurement of the water rebound effect of irrigation technology in Iranian agriculture - َAhmad Soltani Zoghi; Gholam Reza Soltani Mohammadi (علوم محیطی)
Introduction: From the perspective of many experts and decision makers, advances in irrigation technology are the main cause of reducing water consumption. Despite these comments, many experts are skeptical of this conclusion. Despite the improvement of irrigation, drainage technologies and improvement of resistant species, the expected reduction in water consumption have never occurred. Can the water rebound effect (WRE) phenomenon be responsible for the lack of reduction in water intake? What is the situation in Iran? This study sought to answer these questions. Material and methods: First, it was necessary to determine the impact of technology on the agricultural sector in the provinces using panel data. The data for the years 1370 to 1396 were used for this purpose. In the next step, using information about water consumption and agricultural sector products over the years under consideration along with the estimated model, the factors of agricultural growth rate, water consumption growth rate, and expected and ongoing savings were calculated. The results of these calculations indicated the rate of water rebound effect in the agriculture sector for 31 provinces and made it possible to discuss the effect of WRE on different regions with a simple comparison. To help policy-makers, the five divisions of the Ministry of Interior was used. Results and discussion: The rate of participation in the development of technology was at a high level of significance (0.043). The agricultural WRE amount in Iran was 319.9%. This study confirmed the effect of WRE on agriculture in the country. The effect of water rebound on all regions of the country was also clearly visible and even some industrial provinces such as East Azerbaijan and Khuzestan were more severely affected by this phenomenon. The highest intensity of WRE was observed in the 3rd region of the country, including the provinces of East Azerbaijan, West Azerbaijan, Ardabil, Zanjan, Gilan and Kurdistan, and the lowest was in the 5th area including Razavi, Southern and Northern Khorasan, Kerman, Yazd, and Sistan and Baluchestan. The intensity of the WRE in the southern and eastern regions of the country was lower than in the northern and western regions. The reason for the relatively lower intensity of this phenomenon in the southern and eastern regions was the limited access to water resources, lack of funding to change the irrigation technology, high-quality land, and specialized labor. Although less intensely, it could be clearly seen that more than 80 percent of the saved water across the country was due to the improvement of technology, which was significant in the field of irrigation technologies, by the same agricultural sector. This it indicates the intensity of the WRE phenomenon on the country's agriculture. Conclusion: The trend of increasing water use in agriculture in the country after applying government support policies and the development of irrigation technologies along with the calculated WRE indicated that improving irrigation technologies, due to the increased productivity, initially reduces water consumption, and also, higher profitability can be achieved by reducing water consumption costs. Increased profit is a motive to expand the crop area, which will increase water consumption, in some cases, more than initial consumption. At this very moment, it is necessary that the authorities focus on controlling the water rebound phenomenon, in addition to the concept of reducing water consumption in the agricultural sector.